2022
DOI: 10.1002/oby.23340
|View full text |Cite
|
Sign up to set email alerts
|

Eating breakfast is associated with weight loss during an intensive lifestyle intervention for overweight/obesity

Abstract: Obesity remains a global epidemic. The prevalence of obesity in US adults was 42.4% in 2017-2018 (1) and it continues to rise. Obesityrelated diseases such as cardiovascular disease and type 2 diabetes mellitus (T2DM) are leading causes of preventable deaths. Despite the existence of effective lifestyle interventions, the disease burden and epidemic of obesity continue to worsen. The recent literature on dietary interventions for weight loss has indicated a conceptual shift from what we eat to when we eat. Obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…This is supported by a systematic review and meta-analysis of observational and longitudinal studies, which showed an increased relative risk of overweight/obesity when breakfast was skipped [ 17 ]. Furthermore, a few studies reported that skipping breakfast was linked to increased levels of fasting insulin, total cholesterol, and low-density lipoprotein cholesterol [ 18 , 19 ]. In agreement with these observations, an intervention study in women with obesity showed that consuming the most calories of the day (700 kcal) during breakfast led to greater weight loss as compared to an evening-loaded diet [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by a systematic review and meta-analysis of observational and longitudinal studies, which showed an increased relative risk of overweight/obesity when breakfast was skipped [ 17 ]. Furthermore, a few studies reported that skipping breakfast was linked to increased levels of fasting insulin, total cholesterol, and low-density lipoprotein cholesterol [ 18 , 19 ]. In agreement with these observations, an intervention study in women with obesity showed that consuming the most calories of the day (700 kcal) during breakfast led to greater weight loss as compared to an evening-loaded diet [ 20 ].…”
Section: Introductionmentioning
confidence: 99%